Engineering Materials : Polymers, Ceramics and Composites - Bhargava, A. K., author 178595 (New Delhi : PHI Learning, 2010)
This text, now in its second edition, continues to provide a balanced practical treatment of polymers, ceramics, and composites, covering all their physical properties as well as applications in industry. The text puts emphasis on developing an understanding of properties, characteristics and specifications of non-metallic engineering materials and focusing on the techniques for controlling their properties during processing. It provides students with the knowledge they need to make optimal selection and use of these materials in a variety of manufacturing applications. The book focuses on structure-properties correlation of materials as it forms the basis for predicting their behavior during processing and service conditions. The text also discusses the recently developed advanced materials. Each chapter includes the questions of fundamental importance and industrial significance, along with their answers. This book is especially designed for Metallurgical and Materials Science students for a course in non-metallic engineering materials. Besides it should prove useful for the students of other engineering disciplines where materials science/materials engineering is offered as a compulsory course.